2008
DOI: 10.1007/s10038-008-0297-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender bias in the multiethnic genetic composition of central Argentina

Abstract: A sample of central Argentina (Córdoba) was genotyped for the first hypervariable region (HVS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 49 publications
10
48
0
3
Order By: Relevance
“…Thus, unlike studies of Y and mitochondrial chromosomes in many other human populations, [47][48][49][50] the Hutterite male and female gene pools are similar with respect to genetic diversity and comparable with respect to their origins, suggesting a similar evolutionary history.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, unlike studies of Y and mitochondrial chromosomes in many other human populations, [47][48][49][50] the Hutterite male and female gene pools are similar with respect to genetic diversity and comparable with respect to their origins, suggesting a similar evolutionary history.…”
Section: Discussionmentioning
confidence: 54%
“…It is noteworthy that most haplotypes (192; 95%) have not been reported earlier (Table 1). 27,39,[40][41][42] The haplotype diversity of the whole control region was 0.9945, with a mean number of pairwise differences of 11.14 and a nucleotide diversity of 0.0655 (see Table 2). Unlike HVR1, HVR2 had 15 sites that showed indels either as a singlepoint insertion (insertion at 180G) or as a part of polymorphic microsatellite (p248-249, p286-291, p303-309 and p311-315) and non-microsatellite (p106-111) tracts.…”
Section: Resultsmentioning
confidence: 99%
“…Considering only the positions at HVR1, this haplotype has been reported earlier once in Latin America. [40][41][42] Interestingly, the polymorphism A16183C was identified in all haplogroup B2 sequences. The haplogroup B2 in this study was further divided in two subgroups, based on transversion A16182C, which was found in 54.1% of the B2 haplotypes.…”
Section: Mitochondrial Haplogroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better evaluate the geographical distribution of the novel haplogroups, we surveyed published and unpublished CR data from a wide range of populations (Ginther et al 1993;Horai et al 1993;Alves-Silva et al 2000;Moraga et al 2000;Lalueza-Fox et al 2001;García-Bour et al 2004;Tajima et al 2004;Cabana et al 2006;Á lvarez-Iglesias et al 2007;Tamm et al 2007;Carvalho et al 2008;Salas et al 2008;Bobillo et al 2010;Catelli et al 2011;Gayà-Vidal et al 2011;Prieto et al 2011;Sans et al 2011;MC Bobillo, unpubl.). This allowed the identification of 103 putative D1g and D1j mtDNAs (Supplemental Table S3).…”
Section: Phylogeographic Patterns Of D1g and D1jmentioning
confidence: 99%